Solve this equation: (x+3)(x+9)

Expert Answers

An illustration of the letter 'A' in a speech bubbles

As written, the expression (x + 3)(x + 9) is not an equation, so there is nothing to solve. This expression may be simplified by multiplying through the parenthesis.

(x + 3)(x + 9) = (x + 3)*x + (x + 3)*9

= x^2 + 3x + 9x + 3*9

= x^2 + 12x + 27

Often expressions such as that given are set equal to zero, in which case there is an equation.

(x + 3)(x + 9) = 0 may be solved by remembering that if a*b = 0, then either a or b must be equal to zero. Thus either x + 3 = 0 or x + 9 = 0, meaning that x = -3 or x = -9

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial